Role of Adenosine A2A Receptors in Modulating Synaptic Functions and Brain Levels of BDNF: a Possible Key Mechanism in the Pathophysiology of Huntington's Disease - Maria Teresa Tebano; Alberto Martire; Valentina Chiodi; Antonella Ferrante; Patrizia Popoli (The Scientific World Journal)
In the last few years, accumulating evidence has shown the existence of an important cross-talk between adenosine A2A receptors (A2ARs) and brain-derived neurotrophic factor (BDNF). Not only are A2ARs involved in the mechanism of transactivation of BDNF receptor TrkB, they also modulate the effect of BDNF on synaptic transmission, playing a facilitatory and permissive role. The cAMP-PKA pathway, the main transduction system operated by A2ARs, is involved in such effects. Furthermore, a basal tonus of A2ARs is required to allow the regulation of BDNF physiological levels in the brain, as demonstrated by the reduced protein levels measured in A2ARs KO mice. The crucial role of adenosine A2ARs in the maintenance of synaptic functions and BDNF levels will be reviewed here and discussed in the light of possible implications for Huntington's disease therapy, in which a joint impairment of BDNF and A2ARs seems to play a pathogenetic role.